2013
DOI: 10.1128/aem.02774-12
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and Salinity-Decoupled Overproduction of Hydroxyectoine by Chromohalobacter salexigens

Abstract: Hydroxyectoine overproduction by the natural producer Chromohalobacter salexigens is presented in this study. Genetically engineered strains were constructed that at low salinity coexpressed, in a vector derived from a native plasmid, the ectoine (ectABC) and hydroxyectoine (ectD) genes under the control of the ectA promoter, in a temperature-independent manner. Hydroxyectoine production was further improved by increasing the copies of ectD and using a C. salexigens genetic background unable to synthesize ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…AAD12 produced 525 mol hydroxyectoine/g dry cell mass. This amount is pretty much comparable to the hydroxyectoine yield by the engineered C. salexigens [29]. Hydroxyectoine yield can further be enhanced by engineering the strain [29,30].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…AAD12 produced 525 mol hydroxyectoine/g dry cell mass. This amount is pretty much comparable to the hydroxyectoine yield by the engineered C. salexigens [29]. Hydroxyectoine yield can further be enhanced by engineering the strain [29,30].…”
Section: Discussionsupporting
confidence: 52%
“…In contrast to our findings, Saum and Müller [12] reported that the moderately halophilic Halobacillus halophilus changed its osmolyte accumulation strategy through exchanging proline by ectoine in the transition from exponential to stationary phase. Another moderate halophile, C. salexigens, accumulated maximum ectoine at 37°C with 17.4% NaCl and maximum hydroxyectoine at 45°C with 14.5% NaCl [29]. Maximum hydroxyectoine accumulation was achieved with 15% NaCl by both C. salexigens and Halomonas sp.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Ectoine excreting and ectoine overproducing mutants of H. elongata are used for the industrial production of ectoine (Kunte et al ., ). Chromohalobacter salexigens has been suggested as an alternative ectoines producer (Fallet et al ., ; Rodríguez‐Moya et al ., ). Thus, the elucidation of C. salexigens mechanisms controlling the synthesis of ectoines is important to design novel metabolic engineering strategies for generating improved strains.…”
Section: Introductionmentioning
confidence: 97%
“…With respect to the latter approaches, ectoine/hydroxyectoine biosynthetic genes have been cloned into plasmids under the transcriptional control of either natural ect or synthetic promoters and transferred to Escherichia coli or Corynebacterium glutamicum host strains (59)(60)(61)(62) or integrated into the chromosomes of biotechnological workhorses such as C. glutamicum (63) or the methylotrophic yeast Hansenula polymorpha (64). In some cases, advanced pathway engineering approaches were also used to enhance the synthetic production of ectoines in homologous and heterologous hosts (62,63,65,66).…”
mentioning
confidence: 99%